MAJAS PERBANDINGAN LAGU BERBAHASA JEPANG - Wamafma, Dance; Iriantini, Sri; Sutanto, Jennifer (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2023)
One of the function of languages are to express emotion. The statement, emotion, the way of thinking is not often poured into a literature especially in songs, poetry, novel, and other literature. In making song, language that is often used is more beautiful, because it is focuses on an emotional aspect, so that the meaning of the song is delivered accurately. This research raises the theme of comparative learning in songs popularized by Ayumi Hamasaki using semantic studies. The problem in this research will be discussed with the stylistic theory, so that the reader can capture the feelings and goals set forth by the author. While semantic theory is used to understand the meanings implied in the lyrics of her songs. In a musical piece, surely song writer has their own colors and shape or characteristic that make the piece unique and liked and also makes the listener feel the power of the language in it.   Keywords: language, stylistic, songs, theme, semantics